2021
DOI: 10.1016/s2214-109x(21)00263-1
|View full text |Cite
|
Sign up to set email alerts
|

Causes and circumstances of maternal death: a secondary analysis of the Community-Level Interventions for Pre-eclampsia (CLIP) trials cohort

Abstract: Background Incomplete vital registration systems mean that causes of death during pregnancy and childbirth are poorly understood in low-income and middle-income countries. To inform global efforts to reduce maternal mortality, we compared physician review and computerised analysis of verbal autopsies (interpreting verbal autopsies [InterVA] software), to understand their agreement on maternal cause of death and circumstances of mortality categories (COMCATs) in the Community-Level Interventions for Pre-eclamps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“… 23 , 24 It was found that the risk of increased maternal mortality for women aged 35 and up was concentrated in a few causes of death, and much of this excess mortality can be avoided. 25 , 26 In connection with the results of this study, the promotional efforts can be carried out in addition to forming good behavior attitudes. Therefore it is also very important to pay attention to the knowledge factor of pregnant women by carrying out health promotion strategies by empowering health cadres, so that the intentions of the pregnant women can be strengthened by adding more knowledge regarding mother's pregnancy care.…”
Section: Discussionmentioning
confidence: 74%
“… 23 , 24 It was found that the risk of increased maternal mortality for women aged 35 and up was concentrated in a few causes of death, and much of this excess mortality can be avoided. 25 , 26 In connection with the results of this study, the promotional efforts can be carried out in addition to forming good behavior attitudes. Therefore it is also very important to pay attention to the knowledge factor of pregnant women by carrying out health promotion strategies by empowering health cadres, so that the intentions of the pregnant women can be strengthened by adding more knowledge regarding mother's pregnancy care.…”
Section: Discussionmentioning
confidence: 74%
“…Our results found that the odd ratio of the agreement for age groups (60-69, 70-79, and >=80 years) increases if the deceased aged 60-69 and 70-79 years compared to deaths aged 34-59 years, and the likelihood tends to decrease if the deceased was >=80 years compared to the reference (aOR: 1. 34 To evaluate the community perceptions of causes of death, CSMFs obtained from the VA using the InterVA-5 model were utilized to assess FRCoD, along with the CSMF absolute differences and their 95% confidence intervals. Table 2 shows that infectious diseases, stroke, and circulatory-related deaths were found to be underestimated as probable causes of death reported by families in relation to the VA reference standard.…”
Section: Resultsmentioning
confidence: 99%
“…The 2016 WHO VA instrument has been updated to contain all the input variables needed by all three software, making their use more consistent and standardized. [28, 34, 35]. In recent years, a series of InterVA models have been created to interpret VA data using Bayesian probabilistic modeling [36].…”
Section: Methodsmentioning
confidence: 99%
“…According to the recent epidemiological estimations, PE impacts 3%–8% of pregnancy women worldwide ( Bouter and Duvekot, 2020 ) and causes serious hazard to the health of mothers and their fetuses. Moreover, it has been generally admitted that PE has remarkable causal relationship with maternal and perinatal mortality, especially in low-income and middle-income countries ( Ives et al, 2020 ; Aukes et al, 2021 ). Globally, PE could result in more than 50,000 maternal deaths annually ( Ananth et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%